STUDI KITAB MANAR AL-QARY SYARAH MUKHTASHAR SHAHIH AL-BUKHARI (KARYA HAMZAH MUHAMMMAD QASIM) - Wildan Taufik (Diroyah : Jurnal Studi Ilmu Hadis, 2018)
Writing to discuss manaar al-qary fi sharih mukhashar shahih al-bukhari's book of scandal to find out the systematics and methodology of its direction. This study uses literature review (library research), the book of mana>r al-qa>ry syarh mukhtashar shahih al-bukhari is a book of syarh which is summarized from the shahih al-bukhari to 1200 hadith only. Sanad was summarized as only thabaqah companion, takhrij al-hadith, systematics of this book is quite simple and makes it easy for readers to understand hadith. The language used is quite easy to understand because it uses popular language.